Cyclooxygenase-2 modulates ER-mitochondria crosstalk to mediate superparamagnetic iron oxide nanoparticles induced hepatotoxicity: an in vitro and in vivo study. Issue 2 (7th February 2020) - Che, Lin; Yao, Huan; Yang, Chuan-Li; Guo, Ni-Jun; Huang, Jing; Wu, Zi-Li; Zhang, Li-Yin; Chen, Yuan-Yuan; Liu, Gang; Lin, Zhong-Ning; Lin, Yu-Chun
Abstract: Mitochondria-associated endoplasmic reticulum (ER) membranes (MAMs) are central microdomains of the ER that interact with mitochondria. MAMs provide an essential platform for crosstalk between the ER and mitochondria and play a critical role in the local transfer of calcium (Ca 2+ ) to maintain cellular functions. Despite the potential uses of superparamagnetic iron oxide nanoparticles (SPIO-NPs) in biomedical applications, the hepatotoxicity of these nanoparticles (NPs) is not well characterized and little is known about the involvement of MAMs in ER-mitochondria crosstalk. We studied SPIO-NPs-associated hepatotoxicity in vitro and in vivo . In vitro, human normal hepatic L02 cells were exposed to SPIO-NPs (2.5, 7.5, and 12.5 μg/mL) for 6 h and SPIO-NPs (12.5 μg/mL) was found to induce apoptosis. In vivo, SPIO-NPs induced liver injury when mice were intravenously injected with 20 mg/kg body weight SPIO-NPs for 24 h. Based on both in vitro and in vivo studies, we found that the structure and Ca 2+ transport function of MAMs were perturbated and an accumulation of cyclooxygenase-2 (COX-2) in MAMs fractions was increased upon treatment of SPIO-NPs. The interaction between COX-2 and the components of MAMs, in terms of IP3R-GRP75-VDAC1 complex, was also revealed. Furthermore, the role of COX-2 in SPIO-NPs-associated hepatotoxicity was investigated by modifying the expression of COX-2. We demonstrated that COX-2 increases the structural and functional ER-mitochondria coupling and enhances the efficacy of ER-mitochondria Ca 2+ transfer through the MAMs, thus sensitizing hepatocytes to a mitochondrial Ca 2+ overload-dependent apoptosis. Taken together, our findings link SPIO-NPs-triggered hepatotoxicity with ER-mitochondria Ca 2+ crosstalk which is mediated by COX-2 and provide mechanistic insight into the impact of interorganelle ER-mitochondria communication on hepatic nanotoxicity.